The Impact of Personal, Sociological and Institutional Influences on Relationship Commitment in the Retail Banking Sector - Che Wel, Che Aniza (2001)
Most previous research in the domain of relationship marketing has focused on the antecedents of loyalty and commitment in the industrial market, distribution channel or consumer goods. This study however, models the antecedents of consumer's relationship commitment in the context of a retail banking service. The success and survival of a commercial bank depends on its bankers ability to understand customers' needs and find effective ways to satisfy them. Having recognized that retail customers are the potential market niche, it is essential for bankers to obtain information concerning their patronage factors towards specific financial institutions.The impact of four key explanatory variables (personal influence, sociological influence, institutional influence, and trust) on relationship commitment are examined. Self-administered questionnaires were used to obtain primary data from respondents consisted of bank consumer occupying the selected dwelling unit in Kuala Lumpur and Petaling Jaya. A final sample of 578, which was obtained from the both areas, was an acceptable representation of the population. The data was tested using (i) Multiple Regression Analysis (ii) Pearson Correlation Analysis, (iii) Path Analysis. The result shows that sociological influences and trust have the most significant direct impact on relationship commitment. Institutional influences give a great impact on personal and sociological influences but it give a small impact on relationship commitment. This result is consistent with the views of Anderson et. al (1976) and Tan and Chua (1986) that the consumer decision to choose their bank are greatly impacted by the sociological factors. The same study conducted in Malaysia by Haron and Ahmad (1992) however found that social factors are the least influential factors if compared to others. In spite of these inconsistencies, the current studies have comes out with a new conceptual model (Model of Determinant of Relationship Commitment) which indicate that Sociological and Personal Influence, as well as Trust are the determinant of relationship commitment in retail banking industry.However, it needs to be noted that the multiple regression analysis results only shows that the four hypothesized variables investigated (personal influence, sociological influence, institutional influence, and trust), only represents 25.5 per cent of the consumer relationship commitment towards their bank. In short, the bankers who seek success must become more and more oriented to understanding consumer behavior in the financial marketplace. Causal factors operative in consumer bank selection and patronization must be identified to optimize bank marketing strategies. The bankers must adopt a more aggressive stance, become more knowledgeable, acquire more skills and be totally committed to nurturing high quality relationship with the consumer.